Multipurpose table kids / Zulkhanain Mat Zain and Norhafizah Rosman - Mat Zain, Zulkhanain; Rosman, Norhafizah (2014)
The necessity of furniture product is now becoming a trend from time to time in accordance of current technology development. Mostly in furniture demand, an increasingly demand for furniture that has more compact and space saving which can be used in limited space. To address this problem furniture designs with multifunction can be used in limited space such as small room. Multipurpose kids table is able to achieve high demand in the world market based on demand from consumers and the problem they faced. The data was analysed based on the questionnaire that had been distributed to one hundred correspondences from people around UiTM Jengka such as staff, lecturer and student. Then data were analysing by SPSS to get the results. Most correspondent give positive feedback to the material used, space saving multifunction concept, suitability of product to customers and the marketable of the product designated. Overall, the multifunction table is well accepted by most of the correspondence since it provides benefits to the users and customers. Other, based on the result of users agrees or prefers to use multipurpose kids table as part of their household items.